Public acceptance in direct potable water reuse: a call for incorporating responsible research and innovation - Karen Moesker; Udo Pesch; Neelke Doorn (Journal of Responsible Innovation)
As global issues such as climate change and diminishing resources become increasingly pressing, water recycling has moved into the focus. However, the successful implementation of Direct Potable Water Reuse (DPR) projects hinges on securing public acceptance, which remains challenging. This paper aims to flesh out possible reasons for the lingering public rejection of DPR. We will do so by conducting a literature review on how public acceptance is understood and what approaches are proposed to enhance it. These approaches are analyzed using Responsible Research and Innovation principles and the `opening up', `closing down' and `leaving ajar' approaches. Our research identifies an overreliance on the controversial information deficit model, closing down large parts of public engagement. We advocate for becoming more inclusive through the `leaving ajar' approach. Particularly, attention should be paid to reflexivity and responsiveness to public concerns to ensure meaningful public engagement.